PENDIDIKAN AGAMA KRISTEN DI TENGAH ARUS POST-MODERN: ESKATOLOGI SEBAGAI FONDASI PEMBENTUKAN KARAKTER - Beni; Monika Kabe'; Marla Epiphania Payung; Yohanis Medi; Elsia (JIP: Jurnal Ilmu Pendidikan, 2026)
Christian Religious Education (CRE) faces complex challenges in the post-modern era characterized by relativism of truth and spiritual identity crisis. This research explores the integration of eschatological understanding in Christian character formation through qualitative methods with a library research approach. Findings indicate that balanced eschatological understanding positively correlates with spiritual vigilance, moral integrity, psychological resilience, and mission engagement. However, contemporary CRE practices reveal critical gaps: fragmentation of eschatological content, dominance of cognitive-doctrinal approaches, and limited educator competence. The research proposes a holistic integration model that positions eschatology as a theological framework integrating the entire curriculum and adopts transformative pedagogy balancing cognitive, affective, and praxis dimensions. This model is designed to address sensationalist eschatological distortions, develop "eschatological imagination" that enables the post-modern generation to live with transformative hope, and form mature Christian character within the "already-not yet" tension of inaugurated eschatology. Integration of eschatology in CRE is not merely doctrinal transfer, but spiritual formation that empowers believers to become agents of renewal in the "space between" incarnation and Parousia.